Chronic pain and infection: mechanisms, causes, conditions, treatments, and controversies. Issue 1 (1st April 2022) - Cohen, Steven P; Wang, Eric J; Doshi, Tina L; Vase, Lene; Cawcutt, Kelly A; Tontisirin, Nuj
Abstract : Throughout human history, infection has been the leading cause of morbidity and mortality, with pain being one of the cardinal warning signs. However, in a substantial percentage of cases, pain can persist after resolution of acute illness, manifesting as neuropathic, nociplastic (eg, fibromyalgia, irritable bowel syndrome), or nociceptive pain. Mechanisms by which acute infectious pain becomes chronic are variable and can include immunological phenomena (eg, bystander activation, molecular mimicry), direct microbe invasion, central sensitization from physical or psychological triggers, and complications from treatment. Microbes resulting in a high incidence of chronic pain include bacteria such as the Borrelia species and Mycobacterium leprae, as well as viruses such as HIV, SARS-CoV-2 and herpeses. Emerging evidence also supports an infectious cause in a subset of patients with discogenic low back pain and inflammatory bowel disease. Although antimicrobial treatment might have a role in treating chronic pain states that involve active infectious inflammatory processes, their use in chronic pain conditions resulting from autoimmune mechanisms, central sensitization and irrevocable tissue (eg, arthropathy, vasculitis) or nerve injury, are likely to cause more harm than benefit. This review focuses on the relation between infection and chronic pain, with an emphasis on common viral and bacterial causes.